POLITENESS STRATEGY IN REQUEST USED IN JAVANESE WEDDING CEREMONY - Syahputra, Muhammad Eka; Saragih, Amrin (Universitas Negeri Medan, 2019)
This study aimed at analyzing the types of politeness strategy in request which represented in Peningsetan/Srah-Srahan event of Javanese Wedding Ceremony. The descriptive qualitative method used to gain the findings of the data. The documentary transcription from recording that event was the source of the data. From that findings, 25 formed requests from 12 utterances has been analyzed. The data found were 12 utterances in the Peningsetan event of Javanese Wedding Ceremony. And from that utterances, 25 sentences classified as requests, which were found throughout transcribing methods, and the results are Bald-on record 4 (16%), and Positive Politeness 21 (84%), and for the Negative and Off-Record Strategy shared 0 amounts. Later on, the positive politeness was the dominant type of politeness since the wedding was a sacred ceremony, the using of positive politeness would be found massively. The instrument of this study was recording the event and transcribing them into list and marking. Positive Politeness dominated because of the events required manners, even in daily life, Javanese used low tones and more polite language to utter the meaning of the speaker.